Perfectionism and performance-related psychobiosocial states: The mediating role of competition appraisals. Issue 5 (4th May 2023) - Ruiz, Montse C.; Appleton, Paul R.; Duda, Joan L.; Bortoli, Laura; Robazza, Claudio
ABSTRACT: Using the multi-states (MuSt) theory as a framework, the present study focused on the individual (personality) antecedents of psychobiosocial states. Psychobiosocial states comprise emotional subjective experiences and their correlates (cognitive, motivational, volitional, bodily, motor-behavioural, operational, and communicative), that can be functional for performance (helpful) or dysfunctional (harmful). Specifically, we examined the relationships between two perfectionism dimensions (perfectionistic strivings and concerns) and functional and dysfunctional psychobiosocial states. The hypothesized mediational role of competitive appraisals was also tested. Participants ( N = 271, 138 female, 133 male, M age = 22.74 ± 7.01) completed questionnaires assessing the targeted variables. Structural equation modelling revealed that perfectionistic strivings were positive predictors of functional states directly and via challenge appraisals. On the other hand, perfectionistic concerns were positive predictors of dysfunctional states directly and via threat appraisals. Results provide support to MuSt theory and extend the literature on the antecedents of athletes' performance-related feeling states. Findings also provide support for the holistic conceptualization of psychobiosocial states encompassing the functionality dimension. The results highlight the importance of developing interventions aimed at helping athletes high in perfectionistic concerns evaluate situations as a challenge (and less of a threat) and increasing their perceived resources. Highlights Perfectionistic strivings positively related to functional psychobiosocial states Perfectionistic concerns positively related to dysfunctional psychobiosocial states Competitive challenge appraisals mediated the relationship between perfectionistic strivings and functional psychobiosocial states Competitive threat appraisals mediated the relationship between perfectionistic concerns and dysfunctional psychobiosocial states